Pengaruh Vitamin C terhadap Peningkatan Hemoglobin (Hb) Darah dan Kelulushidupan Benih Ikan Kerapu Bebek (Cromileptes altivelis) - Siregar, Yusni Ikhwan; Adelina, Adelina (Jurnal Natur Indonesia, 2009)
This research was conducted from Maret until June 2008, in Big Hall of Development Marine Aquaculture Lampung.The research used experimental methodology, with 4 treatments and 3 replications. The aimed of research are toknow effects of vitamin C to increase a haemoglobin of blood and survival rate and measured effective C vitaminin prawn of humback grouper. The result showed that the highest haemoglobin rate of at PC (2 g/kg prawn), equalto 0,915 g/100 mL. The lowest haemoglobin found at treatment PA. equal to 0,066 g/100 mL. Result of variansianalysis indicate that addition of vitamin C at food give influence to increase the haemoglobin rate (P<0.05).Survival rate after experiment are 100 %. Parameter of water quality of were: temperature 29.3-30.2 oC, pH 7.81-8.27, salinitas 31-32 psu, DO 3,65-5 mg/L, and ammonia content (NH 3) 0.044-0.069 mg/1